Extreme thermal resistance of phages isolated from dairy samples: updating traditional phage detection methodologies - Capra, María Luján (2013)
Starter culture failures due to bacteriophage attacks reduce product quality and may cause financial losses. It was the aim of this work to revise and update the Standard IDF microbiological methodology for phage detection which includes a mandatory control, treated for 15 min at 90 ºC for discrimination of phage- and non-phage inhibitors. Phages specific for Lactococcus lactis, Streptococcus thermophilus, Lactobacillus casei and Lactobacillus paracasei were investigated to establish a reliable heat-treatment for the processing of industrial dairy samples suspected of containing phages. A prolonged heating-step of 45 min at 90 ºC is proposed.